THE DEVELOPMENT OF THE METHODOLOGY OF THE 2ND – 13TH CENTURY HIJRI ULAMA IN UNDERSTANDING HADITH - Ghozaly, Moh. Yusni Amru (Nabawi: Journal of Hadith Studies, 2023)
So far, the focus of the ummah on the study of the methodology used by the ulemas in taking their position as their thought process in producing legal products has not been carried out too muc, In fact, the methodology of the Ulama II-XIII is the core of ijtihad which must be explored to be studied and developed in order to answer the contemporary problems of the growing ummah. This article aims to explore and examine the methodological components used by the Ulama in that period. Through these components, the author also describes the development of methodology from time to time, related to concepts, styles, to the author's fanatical tendencies in their works. Based on literature research with a content analysis approach, the authors identify and select books that fall into the category of fiqh al-hadith. The writer finds the conclusion that the presence of the works of scholars of the II-XIII centuries dominantly influenced the development of methods of understanding hadith from time to time. From their work it can be seen the tendency of the schools of the Salaf scholars to draw legal conclusions methodologically, making it easier for contemporary hadith reviewers to read the jurists' thought maps and the stages of their istinbat from time to time. The study of fiqh al-hadis is growing after the emergence of hadith books using the tabwib al-fiqh method. [Selama ini fokus para sarjana hadis dan pengkaji Islam terhadap kajian metodologi yang digunakan para ulama dalam beristinbat sebagai proses berpikir mereka dalam melahirkan produk hukum, belum terlalu banyak dilakukan. Padahal, metodologi ulama salaf abad II-XIII Hijriyah adalah core ijtihad yang harus digali untuk dipelajari dan dikembangkan demi menjawab problem-problem kontemporer umat yang terus bertambah. Artikel ini bertujuan untuk menggali dan mengkaji komponen metodologi yang digunakan oleh ulama dalam periode tersebut. Melalui komponen-komponen tersebut, penulis juga menguraikan perkembangan metodologi dari masa ke masa, terkait konsep, corak, hingga kecenderungan fanatis pengarang dalam karya-karya mereka. Berbasis penelitian pustaka dengan pendekatan analisis konten, penulis mengidentifikasi dan memilih kitab-kitab yang masuk dalam kategori fiqh al-hadis,. Penulis menemukan kesimpulan bahwa kehadiran karya-karya ulama abad II-XIII , secara dominan memengaruhi perkembangan metode memahami hadis dari masa ke masa. Dari karya mereka dapat diketahui kecenderungan mazhab para ulama salaf dalam mengambil kesimpulan hukum secara metodologis, sehingga memudahkan para pengkaji hadis masa ini untuk membaca peta pemikiran fuqaha dan tahapan istinbat mereka dari masa ke masa. Kajian fiqh al-hadis semakin berkembang pasca munculnya kitab-kitab hadis dengan metode tabwib al-fiqh.]